AKIBAT HUKUM YANG DI TIMBULKAN DARI SUATU PERKAWINAN BEDA AGAMA DI INDONESIA (Analisis Penetapan No. 91/Pdt.P/2022/PN Bks) - Murnita, Eva; Siregar, Abdul Rahman Maulana; Aspan, Henry (JURNAL KELUARGA SEHAT SEJAHTERA, 2025)
The reality in the life of society, interfaith marriages occur as an undeniable reality. In practice, many couples want to live together but do not get married because they are based on different religions or beliefs. There are also couples who have lived together or "kumpul kebo" because of a reason in their relationship, namely different religions. The type of research is normative legal research. In accordance with Article 34 and Article 36 of Law Number 24 of 2013 concerning Population Administration, the marriage of Applicant I and Applicant II was carried out in a Christian manner, so the court ruling must be reported by the applicants to the Population and Civil Registration Service of Bekasi City no later than 60 days since the court ruling has permanent legal force and then the Civil Registration Officer records the Marriage Certificate Register and issues an extract of the marriage certificate and is given to the Applicants.